2009
DOI: 10.1176/appi.ap.33.4.296
|View full text |Cite
|
Sign up to set email alerts
|

Burnout, Perceived Stress, and Depression Among Cardiology Residents in Argentina

Abstract: Cardiology residents in Argentina exhibit high levels of burnout, perceived stress, and depressive symptoms, which warrants greater attention to the psychological needs of residents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
2
8

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 47 publications
2
23
2
8
Order By: Relevance
“…The Perceived Stress Scale (PSS) used in this study is a psychological model 16 characterized by measuring the overall perception of stress. It presents high convergent validity with scales which measure symptoms of anxiety, depression and burnout syndrome 19,29 , and which measure stress according to their consequences (morbidity symptoms and conditions) 25 . In this perspective, the results of the present study are potentially relevant, since they were obtained from a scale capable of inferring clinical consequences resulting from dysfunctional levels of stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Perceived Stress Scale (PSS) used in this study is a psychological model 16 characterized by measuring the overall perception of stress. It presents high convergent validity with scales which measure symptoms of anxiety, depression and burnout syndrome 19,29 , and which measure stress according to their consequences (morbidity symptoms and conditions) 25 . In this perspective, the results of the present study are potentially relevant, since they were obtained from a scale capable of inferring clinical consequences resulting from dysfunctional levels of stress.…”
Section: Discussionmentioning
confidence: 99%
“…From the group of respondents, approximately one out of four presented increased risk of stress related symptoms and clinical conditions 15,18,19,21,26,29,32 . Fifty-two percent of professionals reported having some kind of health problems, although those cannot be attributed exclusively to stress, given the cross-sectional nature of the study.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst burnout in health professions is a frequent area of study in Spain and less so in Latin America, the studies performed in both regions are often studies of prevalence showing high levels of burnout (Gandini, Paulini, Marcos, Jorge, & Luis, 2006;Gil-Monte & Marucco, 2008;Grau, Suñer, & García, 2005;Silva & Menezes, 2008) that may vary in function of the criteria applied due to transcultural influences (Gil-Monte & Marucco, 2008). Burnout is high in these nations especially in resident doctors, who show high levels of emotional exhaustion and signs of depression (Martins et al, 2011;Waldman et al, 2009). We are not aware of similar studies that analyse the adverse work-related consequences of burnout in these nations, although there are studies that found a correlation between burnout and worse scores in perceived quality of life and health impacts (Mingote, Moreno, & Gálvez, 2004;Schwartzmann, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Most importantly, studies have suggested that occupational stress is strongly associated with burnout in specific professional areas, such as nurses 5) and teachers 6) . Physicians, as one of the most competitive professions in the world, have also been reported to experience high levels of stress and burnout 7) . Understanding the burnout levels of physicians and the contributing factors and predictors can be an effective approach to both reducing the health risks among physicians and increasing the quality of health services provided to their patients.…”
mentioning
confidence: 99%